Bahamian Bush Medicine: Fact or Folklore - Gibson, Edith (International Journal of Bahamian Studies, 2015)
The practice of bush medicine in The Bahamas is shrouded in mystery. This literature review is not an attempt to verify or disclaim the beliefs as to the authenticity of the healing powers of native plants but rather to give a brief informative overview of the rich cultural heritage of the Bahamian people. The sources used in this review include statements from local inhabitants whose belief systems are so deeply entrenched that they are confident that their very survival and that of their ancestors hinged on the medicinal powers of bush medicine. Included is historical evidence explaining why bush medicine became an integral part of Bahamian culture as well as scientific evidence of its effectiveness and curative properties.